The relationship between rural credit and member loyalty in a credit cooperative in the municipality of Rondinha, RS, Southern Brazil - Cazzaroto, Tiago; Grando, Tadeu; Gomes, Débora Gomes de; Corrêa, Suelen (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Objective: The study aims to verify the relationship between rural credit and member loyalty in a credit cooperative in Rondinha, RS, Southern Brazil. Methodology: The research was characterized as exploratory. 44 family farmers from the municipality of Rondinha, RS, Southern Brazil, who are members of a credit cooperative and took out rural credit in the 2020/2021, and 2021/2022 harvests participated in the research. The analysis was based on the Swedish model of loyalty analysis, which was originally developed for industry and later used in credit cooperatives. Results: The results indicate that rural credit made available by the researched cooperative influences the loyalty of producers. The main reason for contracting rural credit was to finance planting. The biggest benefit of this type of credit is the security and viability of production. Rural credit makes members hire other services from the institution, such as insurance, capitalization bonds, and investments, bringing the relationship between cooperative members and cooperatives even closer. Study contributions: The research demonstrates that rural credit is a strategy for attracting, retaining, and strengthening relationships with cooperative members, because rural credit positively influences all these areas. Furthermore, the study demonstrates that rural credit can be used by institutions as a powerful relationship tool ensuring customer loyalty, launching a new strategic outlook regarding the importance of rural credit as a differentiator in relationships with customers/associates, increasing the competitiveness of the cooperative or financial institution.